Analysis of immune, microbiota and metabolome maturation in infants in a clinical trial of Lactobacillus paracasei CBA L74-fermented formula - Roggero, Paola; Liotto, Nadia; Pozzi, Chiara; Braga, Daniele; Troisi, Jacopo; Menis, Camilla; Giannì, Maria Lorella; Berni Canani, Roberto; Paparo, Lorella; Nocerino, Rita; Budelli, Andrea; Mosca, Fabio; et al. (Nature communications, 2020)
Mother’s milk is the best choice for infants nutrition, however when it is not available or insufficient to satisfy the needs of the infant, formula is proposed as an effective substitute. Here, we report the results of a randomized controlled clinical trial (NCT03637894) designed to evaluate the effects of two different dietary regimens (standard formula and Lactobacillus paracasei CBA L74-fermented formula) versus breastfeeding (reference group) on immune defense mechanisms (primary endpoint: secretory IgA, antimicrobial peptides), the microbiota and its metabolome (secondary outcomes), in healthy full term infants according to the type of delivery ( n = 13/group). We show that the fermented formula, safe and well tolerated, induces an increase in secretory IgA (but not in antimicrobial peptides) and reduces the diversity of the microbiota, similarly, but not as much as, breastmilk. Metabolome analysis allowed us to distinguish subjects based on their dietary regimen and mode of delivery. Together, these results suggest that a fermented formula favors the maturation of the immune system, microbiota and metabolome. Milk breastfeeding and prebiotic-supplemented formulas have varying effects on the infant gut microbiome. Here, in a randomized controlled clinical trial, the authors investigate the effects of a Lactobacillus paracasei -fermented formula on the immune defense mechanisms, microbiota and its metabolome in full term infants.